The Digital transformation of the fitness sector : a global perspective - García-Fernández, Jerónimo; Valcarce-Torrente, Manel; Mohammadi, Sardar; Gálvez Ruiz, Pablo (Emerald Publishing Limited, 2022)
The fitness sector is a growing economy where suppliers, managers and consumers are in continuously evolving relationships, and in which technology plays a key role in optimization. The Digital Transformation of the Fitness Sector highlights the challenges and opportunities of digitalization uncovered in the wake of recent global challenges in countries around the world. The innovations that have arisen during the COVID-19 pandemic have led to a digital transformation of sports services: facilitating interactions between trainers and consumers, establishing social media as a means of boosting a sector already witnessing great growth, and organising exercise spaces. Yet, as explored by the authors in this edited collection, disparities in accessibility to economic and digital resources that enable digitalization vary depending on the providers, the managers, and the geographical situation facing the organization. With contributions from leading academics and professionals, The Digital Transformation of the Fitness Sector is an excellent read for all practitioners working in fitness technologies, sports marketing, sports management, researchers, and students.